Inhospital outcomes of myocardial infarction in patients receiving direct oral anticoagulants - M. G. Chashchin; A. Yu. Gorshkov; O. M. Drapkina (Столичная издательская компания, 2023)
Aim. To evaluate the clinical course and inhospital outcomes of myocardial infarction (MI) in patients receiving continuous direct oral anticoagulant (DOAC) therapy.Material and methods. Data from 390 patients treated for MI were included in the analysis. The mean age was 64.1±12.8 years. The majority were men (61,5%; n=240). All patients underwent standard diagnostic and therapeutic procedures according to clinical guidelines, including coronary angiography and percutaneous coronary intervention when indicated. Clinical, anamnestic and laboratory data (including C-reactive protein level, troponin I, coagulation test) were analysed. The inhospital course of MI, mortality and incidence of complications were evaluated.Results. Patients were divided into two groups according to DOAC therapy received. The main group included 41 patients with constant DOAC intake, while the control group consisted of 349 patients not receiving DOAC. Patients aged 65 years and older accounted for 68,3% (n=28) of the main group (p=0,0033), with a high proportion of cerebral circulation disorders and venous thrombosis (p<0,01). Atrial fibrillation was diagnosed in 75,6% (n=31) of patients in the main group (p<0,0001). ST elevation MI (STEMI) was seen in 39,0% (n=16) of cases in the main group and 47,3% (n=165) of cases in the control group (p=0,3161). As        a result, 85,4% (n=35) of patients in the main group had a high GRACE-1 risk, compared to 50,4% (n=176) in the control group (p<0,0001). The two groups did not differ significantly in the severity of heart failure (p=0,1549). ST-segment resolution on admission electrocardiogram was observed in 43,8% (n=7) of the main group and 18,1% (n=30) of the control group (p=0,0238). According to coronary involvement severity and the type of antegrade flow in the infarct-related artery, patients in both groups were comparable (p>0,05). Prior DOAC administration had no significant effect on the incidence of gastrointestinal bleeding (odds ratio (OR), 3,96 (95% Confidence Interval (CI) 0,76-20,66)) and mortality (OR 1,47 (95% CI 0,37-5,85)) during hospitalization.Conclusion. Patients with MI who received continuous DOAC therapy had significantly more frequent ST-segment resolution at hospital admission compared with patients who did not receive DOAC. DOAC administration had no significant effect on mortality and incidence of inhospital complications of MI.